Comparison of the complications of traditional 12 cores transrectal prostate biopsy with image fusion guided transperineal prostate biopsy - Huang, Haifeng (BMC Urol, 2016)
BACKGROUND: To compare the complications of traditional transrectal (TR) prostate biopsy and image fusion guided transperineal (TP) prostate biopsy in our center. METHODS: Two hundred and fourty-two patients who underwent prostate biopsy from August 2014 to January 2015were reviewed. Among them, 144 patients underwent systematic 12-core transrectal ultrasonography (TRUS) guided prostate biopsy (TR approach) while 98 patients underwent free-hand transperineal targeted biopsy with TRUS and multi-parameter magnetic resonance imaging (mpMRI) fusion images (TP approach). The complications of the two groups were presented and a simple statistical analysis was performed to compare the two groups. RESULTS: The cohort of our study include242 patients, including 144 patients underwent TR biopsies while 98 patients underwentTP biopsies. There was no significant difference of major complications, including sepsis, bleeding and other complication requiring admissionbetween the two groups (P > 0.05). The incidence rate of infection and rectal bleeding in TR was much higher than TP (p < 0.05), but the incidence rate of perineal swelling in TP was much higher than TR (p < 0.05). There were no significant differences of minor complications including hematuria, lower urinary tract symptoms (LUTS), dysuria, and acuteurinary retention between the two groups (p > 0.05). CONCLUSION: The present study supports the safety of both techniques. Free-handTP targeted prostate biopsy with real-time fusion imaging of mpMRI and TR ultrasound is a good approach for prostate biopsy. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12894-016-0185-z) contains supplementary material, which is available to authorized users.